2020
DOI: 10.3389/fneur.2020.00930
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal IL-4 Administration Alleviates Functional Deficits of Periventricular Leukomalacia in Neonatal Mice

Abstract: Background: Periventricular leukomalacia (PVL) is the major form of brain injury in premature infants. Currently, there are no therapies to treat PVL. Several studies suggested that polarization of microglia, a resident macrophage-like immune cell in the central nervous system, plays a vital role in brain injury and recovery. As an important mediator of immunity, interleukin-4 (IL-4) has critical effects on many immune cells, such as astrocytes and microglia. Increasing evidence shows that IL-4 play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Norden et al demonstrated that repeated LPS injections (at regular intervals) did not magnify the inflammatory reaction, but instead stimulated the neuroprotective effect of microglia, suggesting that the protective effect of microglia may be time-dependent ( 49 ). A brain injury could surely activate microglia, and the M2-to-M1 microglial transition only occurred in the acute phase, but after a certain time, M2 started to dominate ( 27 , 50 ). We speculate that in our WMI-induced cerebral palsy model, such a time demarcation also exists.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Norden et al demonstrated that repeated LPS injections (at regular intervals) did not magnify the inflammatory reaction, but instead stimulated the neuroprotective effect of microglia, suggesting that the protective effect of microglia may be time-dependent ( 49 ). A brain injury could surely activate microglia, and the M2-to-M1 microglial transition only occurred in the acute phase, but after a certain time, M2 started to dominate ( 27 , 50 ). We speculate that in our WMI-induced cerebral palsy model, such a time demarcation also exists.…”
Section: Discussionmentioning
confidence: 99%
“…Both in animals and humans, it has been found that males are more likely to show increased expression of inflammatory indicators and corresponding neurobehavioral symptoms in inflammatory encephalopathy, while females show resilience to neuroinflammation and less severe phenotype ( 51 53 ). Lin-Chao Yu et al used male mice when studying the therapeutic effect of IL-4 on periventricular leukomalacia to avoid the bias of gender in the experiment ( 50 ). In a detailed study of mice microglia, researchers found that a small cluster of extremely specific microglia is enriched in females, which is different from males, and sex only had little effect on microglia diversity ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation